BS35 Novel insights into the use of platelet releasate as a therapeutic approach for tissue regeneration. (May 2019) - Matsakas, Antonios; Scully, David; Sfyri, Peggy; Verpoorten, Sandrine; Wilkinson, Holly; Aburima, Ahmed; Gutierrez, Laura; Acebes Huerta, Andrea; Mitchell, Robert; Patel, Ketan; Hardman, Matthew
Abstract : Aim: Restoration of dysfunctional tissue using platelet-based applications has become an attractive field of research. Due to the cost and safety of such approaches to deliver growth factors in injured tissue; many studies have investigated their potential in regenerative medicine. However, the mechanisms involved in platelet-mediated regeneration are currently poorly understood. The aim of this study was to determine the effect of platelets on cardiac and skeletal myoblast proliferation and differentiation in vitro and establish the role of platelets in skeletal myogenesis ex vivo and in vivo. Methods: Platelet releasate was optimised for improved cell-specific proliferation and differentiation through proliferation assays, immunohistochemical biomarkers, gene and protein expression and proteomics. Mechanistic insights into the effects of platelet secretome interaction with satellite cells, myoblasts, myotubes and myofibres were established through culture with key growth factor inhibitors. Translational aspects of platelet releasate were tested in an in vivo model of injured murine skeletal muscle. Optimisation was next conducted for several other cell types such as cardiomyocytes, human dermal fibroblasts, keratinocytes and chondrocytes. Finally, the platelet secretome from a murine model of thrombospondin-1 (TSP-1) deficiency - a potent angiostatic and pro-inflammatory factor – was studied. Statistics were performed by one-way ANOVA followed by a Tukey's post-hoc. Results: Platelet releasate dose-dependently stimulates myoblast proliferation and temporally stimulates differentiation. Proteomics reveals that PDGF and VEGF ligands are present in higher concentrations for PAR-1- versus collagen- or thrombin- stimulated platelet secretomes. Inhibiting these ligand binding sites dose-dependently inhibits myoblast proliferation and differentiation. We have shown here for the first time that muscle stem cell markers for ex vivo proliferation and cell fate lineage (Cyclin D1 and Scrib, respectively) are upregulated when exposed to platelet releasate. Furthermore, the translational aspect of platelet releasate to an in vivo model shows accelerated regeneration. We show novel data that optimised platelet releasate can stimulate cardiomyocyte, human dermal fibroblast and chondrocyte proliferation and differentiation. Furthermore, we report for the first time that depletion of TSP-1 from platelet releasate promotes a more potent myoblast proliferation compared to wild-type. Conclusion: Platelet releasate is a powerful stimulant in many tissues for angiogenesis and cellular proliferation. Tissue-specific optimisation of the platelet preparation method is a critical step in producing an efficient biomaterial for regenerative medicine. Customisation of platelet releasate such as depletion of TSP-1 opens a new avenue for optimised regeneration. Conflict of interest: None